Bisexuality and the Western Christian Church The Damage of Silence - Shepherd, Carol A. (Palgrave Studies in Lived Religion and Societal Challenges, 2019)
This book critically examines the lived experiences of bisexual Christians across a range of Christian traditions in the UK and the USA. Shepherd assesses whether current data on elevated rates of depressive illnesses among bisexual people also apply to the bisexual Christian community. Drawing on data collected by the author on bisexual Christians across the lifespan, the book uncovers shocking incidences of biphobia and bi erasure in the Church. Widespread ignorance among pastors of middle sexualities outside of the hetero-/homonormative binary is revealed as well as a corresponding absence of appropriate support resources. Bisexuality and the Western Christian Church will be of interest to students and scholars across a range of disciplines, including gender studies, applied theology, sociology and social psychology. It is also important reading for clergy, and LGBT faith organisations. With a Foreword by Eric Anderson, Professor of Sport, Masculinities, and Sexualities, University of Winchester, UK.